Government reform: successes, mistakes, and the road ahead - Consejo Consejo Editorial (Thēmis, 2016)
In this interview, the interlocutor analyzes, in general terms, which are the issues that the government reform involves, mainly in three important fields: civil service reform, public contracting system reform, and promotion of the private investment. Thus, the interlocutor criticizes the way the reforms in some areas have been executed; mentions which are, from his perspective, the successes of some reforms; and outlines proposed solutions for the road ahead for the government modernization.